Breaking the Silence - Abigail S. Dubovi BA; Yue Li MS; Jessica L. Martin PhD (American Journal of Men's Health, 2016)
Men remain largely underrepresented in the eating disorder literature and few studies have investigated risk factors for disordered eating among men. The current study examined associations between Big Five personality traits and eating disorder symptoms in a sample of college men (N = 144). Participants completed the Eating Disorder Diagnostic Scale and Ten Item Personality Inventory online. Results suggested that openness was positively associated with purging-type behaviors and that emotional stability was positively related to symptoms of anorexia nervosa and global eating pathology. Findings highlight the prevalence of eating disorder symptoms among college men and suggest that these symptoms are associated with a different constellation of personality traits than is typically reported among women. Implications for targeted prevention and intervention programs and future research are discussed.